Respuestas
Respuesta dada por:
1
Denisse,
Es una ecuación exponcial. Aplicamos propiedades operacionales de potencias
![3^{4t -2} =3^2.3^4 \\ \\ 3^{4t-2}= 3^{2+4} =3^6 \\ \\ 4t-2=6 \\ \\ 4t=6+2 \\ \\ t= \frac{8}{4} 3^{4t -2} =3^2.3^4 \\ \\ 3^{4t-2}= 3^{2+4} =3^6 \\ \\ 4t-2=6 \\ \\ 4t=6+2 \\ \\ t= \frac{8}{4}](https://tex.z-dn.net/?f=+3%5E%7B4t+-2%7D+%3D3%5E2.3%5E4+%5C%5C++%5C%5C++3%5E%7B4t-2%7D%3D+3%5E%7B2%2B4%7D+%3D3%5E6+%5C%5C++%5C%5C+4t-2%3D6+%5C%5C++%5C%5C+4t%3D6%2B2+%5C%5C++%5C%5C+t%3D+%5Cfrac%7B8%7D%7B4%7D+)
respuesta
Última alternativa
Es una ecuación exponcial. Aplicamos propiedades operacionales de potencias
Última alternativa
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años